Effectiveness of brain gym and writing therapy in behavioral hyperactivity on pre school-age children with ADHD in school for children with special needs (SLB) ABCD kuncup mas of Banyumas - Atika Dhiah Anggraeni; Suherman Suherman; Titin Sutini (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
ADHD is a condition common in children manifested with less concern , impulsive , and hiperaktifitas who do not according to the development of. The purpose of this study is to identify the effectiveness of write therapy and brain gym to the behavior of preschool hyperactivity in children with ADHD. Design research quasy-eksperiment approach in pre- posttest without control group design for 12 children aged pre schools were using total of sampling. This research instruments SPPAHI use of the instruments. Statistical tests use the different 2 mean. The results of the study showed there is a difference in the effectiveness of brain the gym and therapeutic writing in behavior hiperaktivitas children aged pre schools with ADHD ( p value 0,007 ).This research could be one of alternative intervention nursing mandiri that can be done to deal with the behavior hiperaktif children adhd good at the school and home.